DECOLONIZATION AND STRENGTHENING OF WAHDAH ISLAMIYAH ORGANIZATION - Tajuddin, Tabrani; Awwaliyah, Neny Muthiatul (Hunafa: Jurnal Studia Islamika, 2022)
This paper seeks to review the anthropology typical of Islam by reviewing the role of the text and its interlation with religious practices in islam before, this paper will focus on the exploration of authority that is fought by the text in guiding the facts of life of the Muslim community. One of the growing phenomena in society is the use of veils. The legal status of the veil for some scholars still leaves the debate. The debate lies in the point of view in understanding and applying the text messages of the Qur'an and hadiths about the veil. The phenomenon of applying veils in the community will then be the focus of this article. The object of the study is to try to present views and applications about the veil in the Wahdah Islamiyah Makassar community. This is because the Wahdah Islamiyah community is one of the communities known and impressed loudly proclaiming the slogan' back to the Qur'an and sunnah in the city of Makassar.